Preparation method and application of zr-mof-based composite material with photothermal effect and defect modification

CN122828762APending Publication Date: 2026-09-29CHINA THREE GORGES UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610881527.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

另一方面,硫化镉(CdS)虽具有可见光响应,但作为单体催化剂时光腐蚀现象严重

Benefits of technology

1. 该发明通过调节剂辅助溶剂热法合成了富含配体缺陷的UiO-66,并利用酸性溶液后处理移除占据缺陷位点的苯甲酸残留,成功暴露配位不饱和的Zr开放位点。在此基础上,首次采用多硫代钼酸盐(如四硫代钼酸铵)通过强Zr-S配位键修饰Zr-O簇节点,将MoS42-牢固锚定于MOF骨架。这一策略不仅改变了Zr-O簇的局域电子结构和电荷分配,还为后续异质结组装提供了稳定的功能化界面,显著提升了催化剂的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122828762A_ABST
    Figure CN122828762A_ABST
Patent Text Reader

Abstract

The application discloses a kind of preparation method and application of Zr-MOF-based composite material with photo-thermal effect cooperation defect modification. The ligand-deficient UiO-66 is prepared by adjusting agent assisted solvothermal method;Then it is post-treated by acidic solution, removes the adjusting agent residues occupying defect sites, exposes unsaturated Zr coordination sites, and is modified by thiomolybdate to obtain Zr coordination modified defect UiO-66. The Zr-oxygen cluster nodes of UiO-66 are effectively activated by defect engineering and coordination modification strategy, and the last modified Zr-MOF is combined with CdS nanomaterial by self-assembly to form a tight heterojunction. The CdS is provided with anchoring site, and the heterojunction interface promotes the efficient separation and transmission of photo-generated carriers. The obtained composite photocatalyst shows excellent activity, selectivity and stability in photocatalytic alcohol selective oxidation reaction, effectively improves the light absorption capacity of material in full spectrum and near infrared region.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to MOFs-based composite material preparation technology and its applications in energy and environmental protection. Specifically, it relates to the modification and preparation of defective UiO-66 with photothermal effect, and the bifunctional application of its heterojunction composite material in photocatalytic alcohol oxidation coupled with hydrogen evolution. Background Technology

[0002] Photocatalysis technology can convert solar energy into chemical energy, providing a sustainable pathway for clean energy production and the synthesis of high-value-added chemicals. The selective oxidation of alcohols to aldehydes or ketones via photocatalysis is an important type of green organic conversion reaction. Traditional thermocatalytic processes often require harsh conditions or the use of saturated oxidants. Utilizing semiconductor photocatalysts to drive alcohol oxidation under mild conditions using sunlight has enormous application potential.

[0003] Metal-organic frameworks (MOFs) have attracted widespread attention in the field of photocatalysis due to their high specific surface area and tunable band structure. Among them, UiO-66 (Zr) has become an ideal catalyst support due to its excellent chemical and thermal stability. However, pure UiO-66 has a narrow light absorption range, and its Zr-O cluster nodes are usually saturated, lacking direct catalytic active sites, resulting in limited photogenerated carrier separation efficiency and a light absorption range mainly limited to the ultraviolet region. By introducing linker defects into the UiO-66 framework through defect engineering, unsaturated Zr sites can be exposed, providing anchoring centers for subsequent functionalization modifications, while simultaneously regulating its electronic structure and band structure. On the other hand, although cadmium sulfide (CdS) exhibits visible light response, it suffers from severe photocorrosion as a monomeric catalyst. Therefore, this invention introduces unsaturated Zr sites into UiO-66 through defect engineering and coordination modification strategies. The microenvironment of the Zr-O cluster is regulated by coordination modification with polythiomolybdate, and a heterojunction is constructed with CdS using these sites as anchor points. This aims to solve the problems of severe photocorrosion and high carrier recombination rate in single materials. At the same time, the coordination modification of tetrathiomolybdate not only optimizes the local electronic environment but also introduces light absorption and photothermal effects in the near-infrared region. The construction of the Z-type heterojunction retains the strong reducing electrons of cadmium sulfide and the strong oxidizing holes of the modified UiO-66, further enhancing the photocatalytic hydrogen evolution activity of the composite material and achieving efficient photocatalytic alcohol oxidation. Summary of the Invention

[0004] This invention provides a method for preparing and applying a photothermal MOF material modified with ligand defect UiO-66. Specifically, polythiomolybdate is used to modify Zr-O clusters via Zr-S coordination bonds, promoting charge redistribution of metal-oxygen clusters and improving the separation and transfer of photogenerated electrons and holes. By constructing a Z-type heterojunction, the oxidation end advantage of the MOF is further utilized, fully leveraging photogenerated electrons and holes. This composite material is used in a redox-coupled bifunctional system to achieve photocatalytic selective oxidation coupling of alcohols to hydrogen evolution reaction.

[0005] The present invention is achieved through the following technical solutions.

[0006] (1) Preparation and modification of defective Zr-MOF: Zirconium source and terephthalic acid were added to DMF, and UiO-66 rich in ligand defects was synthesized by solvothermal method with benzoic acid as a regulator. The obtained UiO-66 was post-treated in acidic solution to remove the regulator residue occupying the defect sites, expose the unsaturated Zr sites, and then soaked in polythiomolybdate solution to obtain Zr site coordination modified UiO-66, denoted as UMS. The Zr salt mentioned in step (1) is selected from one or more of zirconium tetrachloride and zirconium oxychloride octahydrate; The solvent used in the solvothermal reaction process is selected from at least one or more of methanol, ethanol, water, DMF, and acetonitrile; The solvothermal reaction temperature is 120-180℃, and the reaction time is 12-48h.

[0007] The polythiomolybdate is selected from at least one or more of ammonium tetrathiomolybdate, potassium tetrathiomolybdate, and sodium tetrathiomolybdate.

[0008] (2) Preparation of cadmium sulfide nanomaterials: Cadmium source and sulfur source are dissolved in ethylenediamine solution, ultrasonicated and stirred evenly, the mixed solution is transferred to a reaction vessel and sealed, placed in a high temperature oven for heating, and after the reaction is completed, the precipitate is collected by centrifugation and washing, and then vacuum dried to obtain cadmium sulfide nanomaterials. The cadmium source mentioned in step (2) is selected from one or more of the manganese nitrate, halide, phosphate and sulfate. The ratio of water to ethylenediamine in the ethylenediamine solution is water: ethylenediamine = (10-30 mL): (10-30 mL), and the molar ratio of cadmium source to sulfur source is (1-2.5): (4-10).

[0009] (3) Preparation of UMS / CdS composite material: The UMS obtained in step (1) and the cadmium sulfide nanomaterial obtained in step (2) are combined in a solvent by self-assembly to form UMS / CdS heterojunction composite material.

[0010] The solvent used in the heterojunction self-assembly method described in step (3) is at least one of water, ethanol, and methanol.

[0011] Another technical solution of the present invention is a MOF photothermal material with Zr open site coordination modification of defective UiO-66 prepared by the preparation method described above. The XRD data of the UMS / CdS composite material has three characteristic diffraction peaks at 2θ=26.7°, 44.6° and 52.5°, which correspond to the (002), (110) and (112) crystal planes of hexagonal CdS, respectively. This corresponds to its PDF card (JCPDS#041-1049). The diffraction peaks of UMS at 7.4°, 8.6° and 25.8° belong to the (111), (200) and (600) crystal planes of UiO-66.

[0012] Another technical solution of the present invention is the application of modified defect UiO-66 and its composite material UMS / CdS as a photocatalyst in the coupling of hydrogen evolution in alcohol oxidation.

[0013] Using a xenon lamp as a light source, the prepared composite material is dispersed in a transparent quartz reactor for photocatalytic hydrogen evolution reaction. The reactor contains deionized water and furfuryl alcohol or other alcohols such as benzyl alcohol (BA), vanillin (VA), and p-nitrobenzyl alcohol (BA-NO2). The mixture is degassed before xenon lamp irradiation to ensure that the reactor is under negative pressure.

[0014] In some preferred embodiments, photocatalytic hydrogen evolution is performed on a photocatalytic activity evaluation system. A 300 W xenon lamp equipped with a cutoff wavelength of 420 nm and an AM 1.5 filter is used as the light source for visible light and simulated sunlight, respectively. Specifically, the catalytic material is ultrasonically dispersed in an alcohol-water solution. Before the reaction, air is removed from the reactor solution and glass system by a vacuum pump to bring the system under negative pressure, and the temperature of the reaction tank is maintained at 279 K by a circulating condenser system. The amount of H2 produced is analyzed hourly by gas chromatography (GC7920-TF2A, Au light, China) and monitored by a thermal conductivity detector (TCD). Organic products in the liquid are analyzed by high performance liquid chromatography (Furi LC5090Plus), and photocatalytic cycle stability experiments are also conducted under the same conditions.

[0015] The volume ratio of furfuryl alcohol to water in the reaction solution is 1:(10-100), preferably 1:60.

[0016] The volume ratio of alcohol to water in the reaction solution is 1:(10-100); the amount of catalyst used is 0.5-2 mg / mL.

[0017] The illumination conditions are a xenon lamp equipped with a filter for simulating sunlight (AM 1.5) or visible light (λ ≥ 420 nm), and the reaction temperature is 5-30℃.

[0018] Photothermal performance testing used a 300 W xenon lamp as the primary light source, equipped with cutoff filters of 420 nm, 700 nm, and AM 1.5 to simulate different illumination conditions of visible light, near-infrared light, and simulated sunlight. The sample powder was placed at a fixed position on the test platform below the center of the light source, ensuring that the dispersion area of ​​all powder samples remained consistent. Temperature changes in the test area were monitored in real time using an infrared thermal imager (Fotric 618C).

[0019] The beneficial effects of this invention are as follows: 1. This invention synthesizes ligand-defect-rich UiO-66 via a regulator-assisted solvothermal method, and successfully exposes coordination-unsaturated Zr open sites by removing benzoic acid residues occupying defect sites through acidic solution post-treatment. Based on this, for the first time, polythiomolybdates (such as ammonium tetrathiomolybdate) are used to modify Zr-O cluster nodes through strong Zr-S coordination bonds, thereby enhancing the MoS4... 2- Firmly anchored to the MOF framework, this strategy not only alters the local electronic structure and charge distribution of the Zr-O cluster but also provides a stable functionalized interface for subsequent heterojunction assembly, significantly improving the catalyst's cycle stability.

[0020] 2. This invention is the first to synthesize a photocatalytic material composed of defective UiO-66 (UMS) modified with thiomolybdate salt and CdS nanorods, constructing a Z-shaped heterojunction composite material UMS / CdS with photothermal effect. Under simulated sunlight, this composite material extends its spectral response range to the near-infrared region due to the nonradiative relaxation photothermal effect introduced by thiomolybdate ions and defect state absorption. The local surface temperature rises rapidly under illumination, reaching 154.9 °C within 300 s, effectively reducing the activation energy of alcohol oxidation. Simultaneously, the unsaturated Zr sites of defective UiO-66 act as Lewis acid sites, activating the alcohol hydroxyl groups and promoting CH bond cleavage; MoS4 2- Clusters provide photothermal effects and hole oxidation sites; CdS provides electron reduction sites. Through the synergistic effect of these three components, the photocatalytic hydrogen evolution rate reaches 4.58 mmol·g⁻¹. -1 ·h -1 It is 40.7 times that of pure CdS, and the selectivity of furfuryl alcohol to furfural is as high as 90.6%. It also shows excellent oxidative coupling hydrogen evolution performance for different alcohols (benzyl alcohol, vanillin, p-nitrobenzyl alcohol, etc.).

[0021] 3. The preparation method of this invention uses widely available raw materials, requires no precious metals, and is low in cost. The regulator-assisted solvothermal method and post-treatment and coordination modification processes are mature and controllable, suitable for large-scale production. The obtained UMS / CdS composite material exhibits excellent light absorption capacity, photothermal conversion performance, and catalytic stability across the full spectrum (UV-Vis-NIR), showing broad application prospects in the green energy and fine chemical fields of photocatalytic selective oxidation of alcohols to produce high-value-added aldehydes / acids while simultaneously generating hydrogen. Attached Figure Description

[0022] Figure 1 The image shown is the XRD pattern of the product obtained in Example 1.

[0023] Wherein, a is the X-ray powder diffraction pattern of UMS; b is the X-ray powder diffraction pattern of CdS and the X-ray powder diffraction pattern of the UMS / CdS composite photocatalyst material.

[0024] Figure 2 The images show SEM images of different products. Specifically, a is an SEM image of UMS nanoparticles; b is an SEM image of CdS nanomaterials; c is an SEM image of the 45UMS / CdS composite photocatalyst material; and d is a TEM image of the 45UMS / CdS composite photocatalyst material.

[0025] Figure 3 The UV-Vis diffuse reflectance absorption spectra of UiO-66, UMS, CdS, and 45UMS / CdS composite photocatalysts are shown.

[0026] Figure 4 Photothermal infrared thermal imaging mapping of CdS and 45UMS / CdS composite photocatalytic materials under simulated sunlight.

[0027] Figure 5 The photocatalytic oxidation of furfuryl alcohol coupled with hydrogen evolution performance of 45UMS / CdS composite photocatalyst material.

[0028] Figure 6 The graph shows the changes in furfuryl alcohol conversion and furfural selectivity over time in the photocatalytic oxidation coupling hydrogen evolution performance of 45UMS / CdS composite photocatalyst material.

[0029] Figure 7 The graph shows the photocatalytic performance of the UMS / CdS composite photocatalyst material in the coupling of different alcohol oxidation processes to hydrogen evolution. Detailed Implementation

[0030] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific implementation examples and accompanying drawings. However, the implementation examples given are not intended to limit the present invention.

[0031] Unless otherwise specified, the experimental and detection methods described in the following implementation examples are conventional methods; unless otherwise specified, the reagents and materials can be purchased from reagent companies.

[0032] Example 1 (1) Preparation and modification of defective UiO-66 (UMS): 0.5 mmol zirconium tetrachloride, 0.5 mmol terephthalic acid and 80 mmol benzoic acid were added to 50 mL DMF and dissolved by ultrasonic stirring. The mixture was then placed in a reaction vessel and heated at 120 °C for 24 h. The product was thoroughly washed to obtain UiO-66 rich in ligand defects. The obtained UiO-66 was post-treated in hydrochloric acid solution to remove benzoic acid occupying defect sites. The product was washed and vacuum dried. Ammonium tetrathiomolybdate was dissolved in 20 mL of solvent until saturated. The filtrate was collected through a syringe filter. The treated UiO-66 was soaked in a saturated ammonium tetrathiomolybdate solution to obtain Zr site coordination modified UiO-66, denoted as UMS. (2) Preparation of cadmium sulfide nanomaterials: 5 mmol of cadmium acetate was dissolved in 50 mL of ethylenediamine-water (1:1) solution, sonicated and stirred until completely dissolved, 10 mL of aqueous solution containing 10 mmol of sodium sulfide was slowly added dropwise, transferred to a reaction vessel and sealed, and heated in a high temperature oven at 160 ℃ for 24 h. After the reaction was completed, the precipitate was collected by centrifugation and washed, and dried under vacuum at 60 ℃ overnight to obtain cadmium sulfide CdS nanomaterials. (3) Preparation of UMS / CdS composite material: 100 mg of UMS obtained in step (1) and cadmium sulfide nanomaterials obtained in step (2) were added to 10 mL of ethanol according to different mass percentages of UMS x% and sonicated for 30 min to be composited by self-assembly. The composite sample was washed multiple times and vacuum dried at 60 °C overnight to obtain UMS / CdS heterojunction composite materials with different proportions, named x UMS / CdS (x=10, 20, 30, 40, 45, 50).

[0033] (4) Preparation of comparative sample UiO-66 / CdS composite material: 100 mg of defective UiO-66 (not modified with ammonium tetrathiomolybdate in step (1)) and cadmium sulfide nanomaterials obtained in step (2) were added to 10 mL of ethanol according to different mass percentages of UiO-66 (x%). The mixture was sonicated for 30 min and then self-assembled. The composite samples were washed multiple times and vacuum dried overnight at 60 °C to obtain UiO-66 / CdS heterojunction composite materials with different proportions, named x UiO-66 / CdS (x=10, 20, 30, 40, 45, 50).

[0034] X-ray powder diffraction was performed on the catalyst prepared in Example 1, and the results are as follows: Figure 1 As shown, the X-ray powder diffraction results for UiO-66 and UMS materials are as follows. Figure 1 As shown in -a, the diffraction patterns were compared with the simulated XRD patterns. Similarly, the XRD patterns of the synthesized cadmium sulfide material were compared with the corresponding PDF cards. The results are as follows: Figure 1 As shown in Figure -b, the sharp and well-corresponding XRD diffraction peaks indicate that the prepared CdS nanoparticles have high crystallinity and purity. The prepared UMS / CdS composite photocatalyst material has no impurity peaks, indicating that the present invention successfully and stably prepared the UMS / CdS composite photocatalyst material. The characteristic diffraction peak positions are almost completely corresponding, indicating that the prepared UMS / CdS composite photocatalyst material has a definite phase composition.

[0035] like Figure 2 The microstructure and elemental composition of the prepared UMS, CdS and UMS / CdS composite materials were investigated using SEM, TEM and HRTEM. Figure 2 -a is the SEM image of UMS, showing regular particle morphology with a diameter of about 100~200 nm. Figure 2 In the -b composite material, CdS exhibits a uniform nanorod shape. Figure 2 The different appearances of the two are still clearly visible in -c, such as Figure 2 As shown in -d, UMS particles are bonded to CdS nanorods.

[0036] Example 2 10 mg of the photocatalyst material (45 μM S / CdS) prepared in Example 1 was ultrasonically dispersed in 80 mL of furfuryl alcohol solution (furfuryl alcohol: ultrapure water = 1:60). Before the reaction, air was removed from the reactor and testing system using a vacuum pump. The reaction temperature was controlled at 279 K using circulating water, and the reaction solution was continuously stirred. A 300 W xenon lamp equipped with a cutoff wavelength of 420 nm and an AM 1.5 filter was used as the light source for visible light and simulated sunlight, respectively. The generated H2 was analyzed hourly by gas chromatography (GC7920-TF2A, Aulight, China), and the amount of H2 generated in the system was analyzed by a thermal conductivity detector (TCD). The solution after the reaction was filtered through an organic filter and the concentrations of the alcohol feedstock and product were analyzed by high-performance liquid chromatography. The furfuryl alcohol conversion rate and furfural selectivity were calculated using the following formula: Conversion(%) = ×100%; Selecivity (%) = ×100%.

[0037] The light absorption properties of the prepared catalyst were tested using UV-Vis diffuse reflectance absorption spectroscopy on anhydrous BaSO4 as a substrate. The results are as follows: Figure 3 As shown, when CdS and UMS are coupled to form a UMS / CdS composite material, the light absorption is improved to a certain extent due to the introduction of UMS with near-infrared response, and the light absorption capacity of the composite material is significantly improved compared with pure CdS.

[0038] Further verification was conducted by testing the photothermal conversion capability of the sample powder under simulated sunlight and near-infrared light using an infrared thermal imaging system. The infrared thermal imaging map of the sample is shown below. Figure 4 As shown, under simulated sunlight, the optimal ratio of 45UMS / CdS exhibits a higher photothermal conversion capacity compared to CdS, reaching a temperature of 154.9 ℃ after 300 s of irradiation. This is due to the introduction of UMS, which has good near-infrared absorption, generating a non-radiative relaxation photothermal effect, which increases the overall temperature under illumination.

[0039] The test results of the photocatalytic furfuryl alcohol oxidation coupled hydrogen evolution performance of the catalyst are as follows: Figure 5 As shown, under simulated sunlight, the optimal ratio of 45UMS / CdS composite photocatalyst can achieve a hydrogen evolution rate of 4.58 mmol g. -1 h -1 Compared with pure CdS, the hydrogen evolution performance is improved by 40.7 times, and the selectivity of furfuryl alcohol to furfural reaches 90.6%, which has a significant advantage and is higher than most existing composite photocatalytic materials.

[0040] Its excellent photocatalytic alcohol oxidation coupled hydrogen evolution performance is due to the construction of Z-type heterojunction: First, the modified UMS has a large specific surface area and a larger photoresponse range, which can effectively adsorb small molecule alcohol substrates. At the same time, it can use near-infrared light to generate additional hot electrons. The photothermal effect increases the reaction temperature of the system and further accelerates the activation of the reaction substrate. Under light irradiation, UMS and CdS are simultaneously photoexcited to generate photogenerated electron-hole pairs. Due to band matching and the built-in electric field, photogenerated electrons in the UMS conduction band rapidly recombine with photogenerated holes in the CdS valence band at the interface. This Z-shaped charge transfer path allows the UMS valence band to retain more strongly oxidizing holes, while the CdS conduction band accumulates more reducing electrons, ensuring the continuous and stable progress of hydrogen reduction and alcohol oxidation reactions. The alcohol oxidation reaction mainly occurs in the UMS valence band. The strongly oxidizing holes enriched in UMS can directly oxidize the α-CH bond of furfuryl alcohol, or generate •OH by oxidizing surface hydroxyl / water molecules, which then attacks the α-CH bond of the alcohol, extracting hydrogen atoms to form a carbon-centered radical intermediate, further oxidizing to furfural. Furthermore, electrons in the CdS conduction band can reduce O2 to generate •O2. - •O2 -In the proton-coupled electron transfer environment at the interface, it can be further converted into •OH. Under the combined action of various free radicals and photogenerated holes, furfuryl alcohol can be efficiently converted into furfural. Similarly, other benzyl alcohols are also oxidized to the corresponding aldehydes through a similar mechanism.

[0041] The above embodiments are merely preferred embodiments provided to fully illustrate the present invention. Those skilled in the art can make various modifications and variations to the present invention without departing from its spirit and scope. Equivalent substitutions or transformations made by those skilled in the art based on the present invention are all within the protection scope of the present invention. The protection scope of the present invention is defined by the claims.

Claims

1. A method for preparing Zr-MOF-based composite materials with synergistic defect modification through photothermal effect, characterized in that, Includes the following steps: (1) Preparation and modification of defective Zr-MOF: Zr salt and terephthalic acid were used as raw materials, and benzoic acid was used as a regulator to assist the solvothermal method to synthesize UiO-66 rich in ligand defects; the obtained UiO-66 was post-treated in acidic solution and then soaked in polythiomolybdate solution to obtain Zr-S coordination modified UiO-66, denoted as UMS; (2) Preparation of cadmium sulfide nanomaterials: Cadmium source and sulfur source are dissolved in ethylenediamine solution, ultrasonicated and stirred evenly, and the resulting mixed solution is sealed and heated to react. After the reaction is completed, cadmium sulfide nanomaterials are obtained by centrifugation, washing and vacuum drying. (3) The UMS obtained in step (1) and the cadmium sulfide nanomaterial obtained in step (2) are combined by electrostatic self-assembly to form a UMS / CdS heterojunction.

2. The method for preparing Zr-MOF-based composite material with photothermal effect synergistic defect modification according to claim 1, characterized in that, The Zr salt mentioned in step (1) is selected from one or more of zirconium tetrachloride and zirconium oxychloride octahydrate; The solvent used in the solvothermal reaction process is selected from at least one or more of methanol, ethanol, water, DMF, and acetonitrile; The solvothermal reaction temperature is 120-180℃, and the reaction time is 12-48h.

3. The method for preparing Zr-MOF-based composite material with synergistic defect modification by photothermal effect according to claim 1, characterized in that, The polythiomolybdate is selected from at least one or more of ammonium tetrathiomolybdate, potassium tetrathiomolybdate, and sodium tetrathiomolybdate.

4. The method for preparing Zr-MOF-based composite material with photothermal effect synergistic defect modification according to claim 1, characterized in that, The cadmium source mentioned in step (2) is selected from one or more of the manganese nitrates, halides, phosphates, and sulfates of manganese. The ratio of water to ethylenediamine in the ethylenediamine solution is water: ethylenediamine = (10-30 mL): (10-30 mL), and the molar ratio of cadmium source to sulfur source is (1-2.5): (4-10).

5. The method for preparing Zr-MOF-based composite material with photothermal synergistic defect modification according to claim 1, characterized in that, The solvent used in the heterojunction self-assembly method described in step (3) is at least one of water, ethanol, and methanol.

6. The Zr-MOF-based composite material with photothermal synergistic defect modification prepared by the preparation method according to any one of claims 1-5, characterized in that, The XRD diffraction peaks of the UMS / CdS composite material are characteristic at 6.7°, 7.4°, 8.6°, 25.8°, 44.6°, and 52.5°.

7. The application of a Zr-MOF-based composite material with photothermal effect synergistic defect modification as described in claim 6 in photocatalytic alcohol oxidation coupled hydrogen evolution.

8. The application according to claim 7, characterized in that, The composite material was dispersed as a photocatalyst in a substrate solution composed of benzyl alcohol and its derivatives-water or furfuryl alcohol and its derivatives-water. The solution was placed in a transparent quartz reactor and a xenon lamp was used as a light source for photocatalytic reaction. Before xenon lamp irradiation, the mixture was degassed to ensure that the reactor was under negative pressure, and the corresponding aldehyde, acid oxidation products and hydrogen were produced. The volume ratio of benzyl alcohol to water in the reaction solution is 1:(10-100).

9. The application according to claim 7, characterized in that, The volume ratio of alcohol to water in the reaction solution is 1:(10-100); the amount of catalyst used is 0.5-2 mg / mL.

10. The application according to claim 7, characterized in that, The illumination conditions are a xenon lamp equipped with a filter for simulating sunlight (AM1.5) or visible light (λ ≥ 420 nm), and the reaction temperature is 5-30℃.